Numerical Investigation of the Effect of Changes in Glass Typeon the Cooling Load in a Building - Sunardi, Cecep; Mitrakusuma, Windy Hermawan; Pradita, Didiet Tricahya; Kasni, Sumeru; Sulaimon, Shodiya (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
Solar radiation enters the building through the glass by both radiation and conduction. The heat passing through the glass is one of the largest cooling loads. Therefore, modifying the glass type, will potentially reduce the cooling load significantly. This numerical study uses Cooling Load Temperature Difference (CLTD) method to calculate the change in cooling load in a five-story hospital. The Glass material was changed from clear glass to coated glass. Based on the calculation of cooling load per hour, from 07.00 to 19.00, it is obtained that the peak load occurs at 17.00, both when using clear glass clear and coated glass. The replacement of clear glass with coated glass results in a 70.0% decrease in radiation cooling load, from 104.59 kW to 31.38 kW. In addition, replacing this type of glass will reduce the total cooling load by 17.0%, from 418.80 kW to 347.57 kW. The decrease in total cooling load will lead to a decrease in the operational cost of the air conditioning system. If it is assumed that the AC system operates at 75% peak load for 16 hours per day, then replacing the glass will reduce electricity costs by approximately Rp. 43.6 million/month.